CREATIVE THINKING USING METAPHORIC LANGUAGE TO IMPROVE POETRY WRITING SKILLS - Marlina Bakri; Aceng Rahmat; Ninuk Lustyantie (English Education Department, 2019)
metaphoric language affect students in improving their poetry writing skills. By taking randomly 176 samples from a student population of 314, data were collected through 3 types of tests and were analyzed by a regression test. The results show that the ability to think creatively has an effect on improving the students' poetry writing skills by 72.9% while the ability to use metaphoric language has an effect of 7.30% on their poetry writing skills. The implications that these effects provide cognitive and practical benefits are also discussed.